How much are we willing to do for the ones we love- impact on caregivers of patients suffering from periprosthetic joint infections: a qualitative study - Dally, Franz Joseph; Prüßner, Franziska; Bludau, Frederic; Gravius, Sascha; Darwich, Ali; Betsch, Marcel (Journal of Bone and Joint Infection, 2026)
Introduction: We aimed to identify and explore the psychological and physical strains that caregivers of patients suffering from a periprosthetic joint infection (PJI) experience. Methods: Twenty-four qualitative semi-structured interviews with people giving care to patients suffering from a PJI were conducted by a single trained interviewer. The interviews were used to identify physical and emotional challenges that caregivers were confronted with. Results: The psychological and physical strains caregivers reported were wide-ranging and included suffering from stress and anxieties, and feelings of hopelessness and helplessness while having to function all the time to the point where, subjectively, caregivers felt as if they gave themselves up. Caregivers were suffering from mental and physical exhaustion as mainly family members and close ones provided the caregiving. Oftentimes an elaborate team effort approach was needed to lighten the caregiving burden. Conclusions: This study shows that caregivers are willing to go above and beyond for their loved ones, while exhausting and exceeding their individual resources. Caregivers of PJI patients deal with major issues. Specifically, we identified (1) conflicts regarding the hospital stay, (2) novel personal challenges, (3) nursing, (4) emotional and psychological consequences, and (5) effects on the relationship. Our research shows that there is a profound need for support during and after hospitalisation, and caring for a PJI patient seems surprisingly similar to caring for a cancer patient. We recommend including the caregivers of PJI patients, and how to better support them, into the PJI treatment guidelines.
CRIS-Team Scopus Importer:2026-02-20